Indole-3-Acetic Acid Producing Yeasts in the Phyllosphere of Legumes: Benefits for Chili Growth - Soponputtaporn, Sopitar; Srithaworn, Moltira; Promnuan, Yaowanoot; Srirat, Piyamat; Chunhachart, Orawan (Trends in Sciences, 2024)
Plant growth-promoting yeast (PGPY), which is associated with plants, has demonstrated the ability to enhance plant growth and crop yield and provide an effective alternative strategy for reducing the extensive use of chemical fertilizers. However, plant development and yield effects of the phyllosphere yeast have received comparatively little research. Therefore, 95 phylloplane yeast were isolated from the leaves of plants in Leguminosae, and their capability to produce indole-3-acetic acid (IAA) in yeast extract peptone dextrose (YPD) broth supplemented with L-tryptophan was evaluated in this research. Forty-two isolates were selected, due to their ability to produce IAA. Among these isolates, 7 showed high IAA production of more than 40 mg/g DW in YPD with tryptophan as the precursor. These strains were identified as Candida tropicalis, Pichia kudriavzevii and Tortispora caseinolytica based on morphological and D1/D2 domain of LSU rDNA sequence analysis. Other plant growth promotion traits, including the solubilization of phosphate, production of ammonia and siderophores and ACC deaminase activity, were also investigated. The results revealed that Candida tropicalis KPS2219 exhibited maximum IAA production of 54.10 mg/g DW, high ammonia production at 1.16 mg/mL and siderophore production. In a greenhouse experiment, the ability of C. tropicalis KPS2219 to enhance the growth of chili seedlings was investigated. The results revealed that seed priming followed by foliar spraying with C. tropicalis KPS2219 significantly increased the root length, shoot length, root dry weight and stem dry weight of the seedlings by 17.72, 29.15, 60 and 46.15 %, respectively, in comparison to those of the uninoculated control. These findings indicate the possibility of C. tropicalis KPS2219 as a bioinoculant to promote plant development and the effectiveness of foliar application. The efficacy of employing yeast consortiums to enhance growth will be investigated for further study. HIGHLIGHTS Phylloplane yeasts with remarkably high IAA production and multiple traits that promote the growth of plants were isolated from the new habitat, legumes. Spraying the yeast cells on the leaves of chili plants accelerated the growth of the plant. GRAPHICAL ABSTRACT